2015
DOI: 10.1680/geot.14.p.118
|View full text |Cite
|
Sign up to set email alerts
|

A bounding surface hysteretic water retention model for deformable soils

Abstract: The paper presents a model that takes into account the influence of void ratio and hydraulic hysteresis on soil water retention. The model is based on the definition of two bounding surfaces, i.e. a main drying surface and a main wetting surface, that delimit the region of admissible soil states in the space of degree of saturation, suction and void ratio. An auxiliary variable, named scaled suction, is introduced to combine the effects of suction and void ratio into a single quantity, so that the main surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…The uniqueness of this relationship between water ratio and suction at high suction (and low saturation) has already been experimentally observed in compacted silts and clays with different degrees of activity [4][5][6]. The above observations are also in agreement with the retention model proposed by Gallipoli (2012) [7] and Gallipoli et al (2015) [8], who suggested that any mechanically-induced change of void ratio will only affect the largest pores while leaving the smaller ones almost unchanged. At high suction (and low saturation), water withdraws in the smallest pores so that any mechanically-induced change of void ratio is unable to cause a variation of water ratio.…”
Section: Resultssupporting
confidence: 85%
“…The uniqueness of this relationship between water ratio and suction at high suction (and low saturation) has already been experimentally observed in compacted silts and clays with different degrees of activity [4][5][6]. The above observations are also in agreement with the retention model proposed by Gallipoli (2012) [7] and Gallipoli et al (2015) [8], who suggested that any mechanically-induced change of void ratio will only affect the largest pores while leaving the smaller ones almost unchanged. At high suction (and low saturation), water withdraws in the smallest pores so that any mechanically-induced change of void ratio is unable to cause a variation of water ratio.…”
Section: Resultssupporting
confidence: 85%
“…The hydraulic law, detailed in Gallipoli et al (2015), describes the hysteretic variation of degree of saturation, caused by changes of suction, (where and are the pore air and water pressures, respectively) and void ratio, . In particular, the variation of the degree of saturation is related to a single independent variable named the "scaled suction" ̅ (Gallipoli et al, 2015), which is equal to the suction scaled by a power function of void ratio :…”
Section: Hydraulic Lawmentioning
confidence: 99%
“…The parameter coincides with the asymptotic slope of the two main curves when the scaled suction tends to infinity in the -̅ plane. This slope must be identical for both curves to ensure the continuity of the stress path at the reversal point of drying-wetting cycles as shown by Gallipoli et al (2015). The physical meaning of all model parameters, together with their range of variation, is discussed in Gallipoli et al (2015).…”
Section: Hydraulic Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…2). In addition, the soil-water retention curve (SWRC) and permeability of the infill will change during shear with its porosity (Mašín 2010;Gallipoli et al 2015;Hashem 2016;Carrier and Beckman 1984). All these factors may cause large variation of suction and saturation values in the shear process under hydraulic-mechanical coupling.…”
Section: Introductionmentioning
confidence: 99%